Moment-knee angle relation in well trained athletes - Ullrich, B.; Brüggemann, G. P. (International Journal of Sports Medicine, 2008)
The purpose of this work was to investigate whether different modes of long-term competitive physical activity cause functional differences in the moment-knee angle relation of the M. quadriceps femoris (QF). Therefore, a sample (n = 40) of young male competitive endurance runners, cyclists, triathletes and tennis players performed isometric maximal voluntary knee extensions (MVC) with their stronger leg at six different knee joint angles while keeping the hip joint angle constant. Muscle activation of QF-muscles during MVC was estimated using surface electromyography (EMG). Moments and EMG data of each subject were normalized to the largest value produced at any knee joint position [% Max.]. No significant differences in the normalized [% Max.] moment-knee angle relation of the QF were found between endurance runners, cyclists and triathletes. Despite few unsystematic exceptions, no functional differences in the normalized moment-knee angle relation of the QF occurred among tennis players and the endurance-oriented athletic groups. Obtained by curve fitting, the optimal knee joint angle for moment production was not significantly different among all athletic groups. We conclude that long-term competitive endurance running, cycling, triathlon and tennis do not provoke functional differences in the moment-knee angle relation of the whole QF.